Legal Protection for Victims of Extortion Crimes: A Study at the Medan Polrestabes - Azrimarisya Putri Zahrul; Nursariani Simatupang; Jaholden, Jaholden (SEAN Institute, 2025)
Cybercrime is becoming increasingly complex in today's digital era, one of which is sextortion, which poses a serious threat to the security and privacy of individuals, particularly women and children. Sextortion is a technology-based sexual crime that exploits a victim's intimate data for blackmail. This study aims to determine the form of sextortion crime, to determine legal protection for victims of sextortion crimes and to determine the obstacles in efforts to provide legal protection for victims of sextortion crimes. This type of research uses an empirical legal research approach. The nature of the research used is descriptive analysis. Using the method of legislative approach related to the legal issues being studied. The results of this study indicate that the legal protection provided to victims of sextortion by the police, including: Provision of legal assistance, Confidentiality of victim identity, Arrest of perpetrators with preliminary evidence, Provision of other assistance in the form of health services, Rehabilitation efforts. Legal protection for victims of crime is an effort to restore losses suffered by victims. Legal regulations in Indonesia cover various aspects of community life in Indonesia, one example is the formation of various Government Regulations and Laws that regulate and guarantee the security of the continuity of community life. For the obstacles themselves there are no, but for the difficulty in revealing this case (profiling), investigators find it difficult to communicate with the victim, where the victim feels embarrassed when communicating because of the problems he experiences which cause fear, anxiety and trauma that he feels during this case.